Environmental Sensing Analytical Techniques for Earth Observation - Lein, James K. (Springer New York : Imprint: Springer, 2012)
Remote sensing is a mature technology that has been largely under- utilized in a world increasing focus on Geographic Information Systems. With the goal of encouraging a wider appreciation of what this science can achieve, Environmental Sensing: Analytical Techniques for Earth Observation introduces the scope and method of remote sensing within the context of environmental analysis and assessment. Written in easy to follow language, the book presents cutting-edge techniques and innovative applications in a manner that is accessible to the non-technical professional. Incorporating extensive use of both the environmental and remote sensing literature, this book can serve as a valuable reference as well as a useful teaching resource in and out of the classroom.  At a time when society is increasingly focused on the vexing issues surrounding global change and environmental sustainability, bringing remote sensing “down to earth” is both a timely and essential step toward enhancing environmental understanding and guide effective environmental decision making.